A critical review of mobile learning integration in formal educational contexts - Pedro, Luís Francisco Mendes Gabriel; Barbosa, Cláudia Marina Mónica de Oliveira; Santos, Carlos Manuel das Neves (International Journal of Educational Technology in Higher Education, 2018)
The use of digital technology in the learning process and teaching practices in formal teaching is highly dependent on the ability of teachers of introducing it without jeopardizing the richness of the classroom environment, namely the attention that students need to follow the flow of argumentation and to guarantee the quality of the inquiring. Although several studies value the importance of technologies in our media-enriched world and the "learn anytime and anywhere" motto associated with mobile learning, we argue that the classroom dynamics are becoming more and more at risk with the addictive dimension brought about by the ubiquitous presence of digital devices and social media in students’ lives. In this article, we will make a critical review of the literature related to mobile learning because there is still a need of more extensive research on the interference of technology in the classroom, especially on how multitasking affects the teacher role in-class as a media orchestrator and learning facilitator. Finally, we will discuss the use of technology in the formal classroom environment, mainly to stimulate a much-needed discussion about the bright-not-so-bright impacts of technology in the teaching and learning process.